Comparison of the solution conformation and dynamics of antifreeze glycoproteins from Antarctic fish. - Lane, A N (2000)
The (1)H- and (13)C-NMR spectra of antifreeze glycoprotein fractions 1-5 from Antarctic cod have been assigned, and the dynamics have been measured using (13)C relaxation at two temperatures. The chemical shifts and absence of non-sequential (1)H-(1)H NOEs are inconsistent with a folded, compact structure. (13)C relaxation measurements show that the protein has no significant long-range order, and that the local correlation times are adequately described by a random coil model. Hydroxyl protons of the sugar residues were observed at low temperature, and the presence of exchange-mediated ROEs to the sugar indicate extensive hydration. The conformational properties of AFGP1-5 are compared with those of the previously examined 14-mer analog AFGP8, which contains proline residues in place of some alanine residues (Lane, A. N., L. M. Hays, R. E. Feeney, L. M. Crowe, and J. H. Crowe. 1998. Protein Sci. 7:1555-1563). The infrared (IR) spectra of AFGP8 and AFGP1-5 in the amide I region are quite different. The presence of a wide distribution of backbone torsion angles in AFGP1-5 leads to a rich spectrum of frequencies in the IR spectrum, as interconversion among conformational states is slow on the IR frequency time scale. However, these transitions are fast on the NMR chemical shift time scales. The restricted motions for AFGP8 may imply a narrower distribution of possible o, psi angles, as is observed in the IR spectrum. This has significance for attempts to quantify secondary structures of proteins by IR in the presence of extensive loops.